Efek Kepemimpinan Inclusive terhadap Keterikatan Kerja: Penjelasan dari Mekanisme Rasa Memiliki - Ria Mariana; Adi Rahmat; Muhammad Rasyid Abdillah (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the effect of inclusive leadership on work engagement with sense of belonging as a mediating variable at the Regional Secretariat of Siak Regency. The research employed a quantitative approach with a census technique involving 136 civil servants. Data were collected through questionnaires and analyzed using Structural Equation Modeling with SmartPLS 3.2.9. The findings reveal that: (1) Inclusive leadership positively and significantly affects work engagement; (2) Inclusive leadership positively and significantly influences sense of belonging; (3) Sense of belonging positively and significantly affects work engagement; (4) Sense of belonging significantly mediates the relationship between inclusive leadership and work engagement. These findings offer theoretical contributions and practical implications for public sector organizations seeking to enhance employee engagement through inclusive leadership strategies